Analysis Of the Effect Of Total Production, International Price, Exchange Rate, and Inflation On the Volume Of Indonesian Rubber Exports, 1980-2018 - Anak Agung Sagung Paramita Devi; Made Kembar Sri Budhi; Ni Nyoman Yuliarmi; Nyoman Djinar Setiawina (Green Publisher Indonesia, 2021)
The purpose of this study is to partially and simultaneously analyze the influence of the variable production quantity, international prices, exchange rates, inflation on the volume of Indonesian rubber exports from 1980 to 2018. The research method uses quantitative methods. Sources of research data from publications of data collected by government officials or departments include the website of the Central Statistics Agency (BPS), Bank Indonesia (BI), the Ministry of Agriculture's Data and Information Center (Pusdatin), Index Mundi. The research location was conducted in Indonesia. The data method used in this study is the non-behavioral observation method. Multiple linear regression is the type of data used in this study as an econometric tool to describe this research and also uses data analysis such as descriptive statistical tests, classical assumptions test, simultaneous test (F test), and partial test (t-test). The results of the analysis in this study indicate that the amount of production, international prices, exchange rates, and both simultaneously and simultaneously have a significant effect on the volume of Indonesian rubber exports during the years 1980-2018. Partially the amount of production has a positive and significant effect on the volume of Indonesian rubber exports in 1980-2018, while international prices, exchange rates and inflation have no significant effect on the volume of Indonesian rubber exports in 1980-2018.